Facial injury management undertaken at US and UK medical treatment facilities during the Iraq and Afghanistan conflicts: a retrospective cohort study - Douglas M Bowley; Joseph DuBose; John Breeze; James G Combes; James Baden; Rory F Rickard; David B Powers (BMJ Open)
Objectives To perform the first direct comparison of the facial injuries sustained and treatment performed at USA and UK deployed medical treatment facilities (MTFs) in support of the military campaigns in Iraq and Afghanistan.Setting The US and UK Joint Theatre Trauma Registries were scrutinised for all patients with facial injuries presenting alive to a UK or US deployed MTF between 1 March 2003 and 31 October 2011.Participants US and UK military personnel, local police, local military and civilians.Primary and secondary outcome measures An adjusted multiple logistic regression model was performed using tracheostomy as the primary dependent outcome variable and treatment in a US MTF, US or UK military, mandible fracture and treatment of mandible fracture as independent secondary variables.Results Facial injuries were identified in 16 944 casualties, with the most common being those to skin/muscle (64%), bone fractures (36%), inner/middle ear (28%) and intraoral damage (11%). Facial injuries were equally likely to undergo surgery in US MTF as UK MTF (OR: 1.06, 95% CI 0.4603 to 1.142, p=0.6656); however, variations were seen in injury type treated. In US MTF, 692/1452 (48%) of mandible fractures were treated by either open or closed reduction compared with 0/167 (0%) in UK MTF (χ2: 113.6; p≤0.0001). US military casualties who had treatment of their mandible fracture (open reduction and internal fixation or mandibulo-maxillary fixation) were less likely to have had a tracheostomy than those who did not undergo stabilisation of the fractured mandible (OR: 0.61, 95% CI 0.44 to 0.86; p=0.0066).Conclusions The capability to surgically treat mandible fractures by open or closed reduction should be considered as an integral component of deployed coalition surgical care in the future.